Strengthening Non-English Teachers’ Ability in Using English as Instructional Language - zaitun, zaitun; Novita, Pipit; Diana, Apriana (English Language in Focus (ELIF), 2024)
This study aimed to prove the effectiveness of communicative approach to strengthen non-English teachers’ speaking ability in using English as their instructional language. The study was carried out at SD Lab-school FIP UMJ, South Tangerang in the even semester of 2023/2024 academic year. There were 30 teachers of all grades participated in this study. This research was mixed-methods with statistics descriptive approach. Both speaking pre-post tests and observation were used in collecting the data. The results of the tests were analyzed by using simple calculation and reported in the form of average score. Meanwhile, the results of the observation were described descriptively. The findings of the quantitative approach revealed that on the average the learners performed better in the post-test and their average score escalated up to 22.17 points from the pre-test. Whereas the results of the observation as part of qualitative approach showed that the learners were able to manage their speaking problems better in which they became more confident, had more vocabularies and were able to construct proper sentences. To conclude, this research work confirmed that communicative approach was effective to strengthen non-English teachers’ speaking ability.